Study on morphometric , meristic and growth patterns Of mystus nigriceps in the pinag luar oxbow - Siska Alemina Ginting; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study aims to understand morphological and meristical characteristics,relative growth and condition factor of Mystus nigriceps living in the Pinang LuarOxbow has been conducted on Januari to Maret 2014. The results There were 132fishes (23-184 mm TL and 2-40 gr) which collected and measured. There are sevencharacters that will be calculated meristic and 27 morphometric characters that willbe measured in this study. Meristical characteristics of fins were as follows D.I.7,P.II.10-22, V.10-12, A.8-9 C.16-23. Twenty seven morphological characteristicswere measured and to understand the growth pattern, each character length wascompared with Total Length (TL) and was reflected as percent of the TL. Therelative growth patterns of the morphological characteristic measured is thecharacteristic growing faster than that of the TL.. Lenght-weight relationship shownthat m. nigriceps male growing isometric and m. nigriceps female allometric positive(male b=2,968 and female 3,092). The water quality shown tremperature range 26 –28 0C, pH was 5, DO 4,6 – 6,2 mg/l, C02 5,8-8,8, brightness 22-49cm, depth 108-520cm. The water quality of fish.Key words : Mystus nigriceps, Pinang Luar Oxbow, morphological characteristic,meristical characteristic